Patient profiles, initial hospital encounter characteristics, and hospital re-encounters of patients with a hospital emergency department visit or inpatient admission for major depressive disorder. (31st December 2022) - Zhang, Qiaoyi; O'Hara, Marguerite; McCormick, Carter; Lingohr-Smith, Melissa; Borentain, Stephane; Mathews, Maju; Joshi, Kruti; Anjo, Joana; Lin, Jay
Abstract: Objectives: To gain a better understanding of the characteristics of patients with a hospital encounter for major depressive disorder (MDD) and evaluate associated hospital resource utilization, hospital charges and costs, and hospital re-encounters. Methods: Adult patients with a hospital encounter (i.e. emergency department [ED] visit only or inpatient admission) with MDD as the primary discharge diagnosis (index event) during July 2018‒March 2019 were selected from the Premier Healthcare Database. Patient characteristics, hospital resource utilization, and hospital charges and costs were evaluated during index events. During a 12-month follow-up, hospital re-encounters (MDD-related and all-cause ED visit only or inpatient readmissions) were examined. Results: The study population included 77, 178 patients with an index hospital encounter (ED visit only: 49.9%; inpatient admission: 50.1%) for MDD. The most common secondary mental health-related diagnosis was suicidal ideation/behavior, which was recorded in 51.8% of patients. The mean age was 38.2 years, 53.0% were female, and 72.1% were Caucasian. Among patients with an ED visit only, the mean index hospital charges and costs were $3, 608 and $639, respectively. Among those with inpatient admissions, the mean length of stay was 4.9 days, and the mean index hospital charges and costs were $17, 107 and $6, 095, respectively. During the 12-month follow-up, 13.3% of patients in the overall study population had an MDD-related hospital re-encounter (primary or secondary discharge diagnosis code indicating MDD); nearly one-third (31.3%) occurred within 30 days post-discharge. During the follow-up, 28.1% had an all-cause hospital re-encounter with 29.7% having occurred within 30 days post-discharge. Limitations: Due to constraints of the Premier Healthcare Database, healthcare resource utilization and costs outside of the hospital could not be evaluated. Conclusions: Patients with a hospital encounter for MDD are relatively young, commonly have suicidal ideation/behavior, utilize substantial hospital resources, and have a high risk for a hospital re-encounter in the 30 days post-discharge.